Analysis of The Effect of Poverty Level, Unemployment, and Population on The Human Development Index in Solo Raya During 2014–2024 - Muhammad Akhsal Daffa Rasendriya; Muhammad Arif (Journal Development Manecos, 2026)
Human development is a key indicator of regional welfare and sustainable development. Understanding the factors that influence the Human Development Index (HDI) is therefore essential for designing effective development policies. This study examines the effects of poverty, unemployment, population, and Gross Regional Domestic Product (GRDP) on HDI in the Solo Raya region, Indonesia, during the 2014–2024 period. The study employs a quantitative approach using panel data regression analysis. To determine the most appropriate estimation model, the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) were compared using the Chow Test and Hausman Test. The results indicate that the Fixed Effect Model is the most suitable model, suggesting the presence of significant regional heterogeneity across districts and the city within Solo Raya. The findings reveal that poverty, population, and GRDP significantly affect HDI, while unemployment has no statistically significant effect. Among the explanatory variables, GRDP exerts the strongest positive influence on HDI, highlighting the importance of economic performance in supporting human development. Population also contributes positively to HDI, indicating the potential role of demographic resources in regional development. The positive relationship between poverty and HDI suggests that government interventions and social protection programs may have mitigated some of the adverse effects of poverty on human development outcomes. These findings imply that improvements in HDI depend not only on economic conditions but also on the effectiveness of local governance in translating economic resources into better education, health, and living standards. Therefore, policies promoting inclusive economic growth, human capital development, and integrated public service delivery are crucial for achieving sustainable human development.